Paediatric bacterial meningitis in the USA: outcomes and healthcare resource utilization of nosocomial versus community-acquired infection. Issue 1 (18th January 2021) - Adil, Syed M.; Hodges, Sarah E.; Charalambous, Lefko T.; Kiyani, Musa; Liu, Beiyu; Lee, Hui-Jie; Parente, Beth A.; Perfect, John R.; Lad, Shivanand P.
Abstract : Introduction. Paediatric bacterial meningitis remains a costly disease, both financially and clinically. Hypothesis/Gap Statement . Previous epidemiological and cost studies of bacterial meningitis (BM) have largely focused on adult populations or single pathogens. There have been few recent, large-scale studies of pediatric BM in the USA. Aim. We examined healthcare resource utilization (HCRU) and associated morbidity and mortality of community-acquired versus nosocomial bacterial infections in children across the USA. Methodology. The IBM MarketScan Research databases were used to identify patients <18 years old admitted to USA hospitals from 2008 to 2015 with a primary diagnosis of BM. Cases were categorized as either community-acquired or nosocomial. HCRU, post-diagnosis neurosurgical procedures, 30-day in-hospital mortality, and complications were compared between groups. Multivariable regression adjusted for sex, age and Gram staining was used to compare costs of nosocomial versus community-acquired infections over time. Results. We identified 1928 cases of paediatric BM without prior head trauma or neurological/systemic complications. Of these, 15.4 % were nosocomial and 84.6 % were community-acquired infections. After diagnostic lumbar puncture (37.1 %), the most common neurosurgical procedure was placement of ventricular catheter (12.6 %). The 30-day complication rates for nosocomial and community-acquired infections were 40.5 and 45.9 %, respectively. The most common complications were hydrocephalus (20.8 %), intracranial abscess (8.8 %) and cerebral oedema (8.1 %). The 30-day in-hospital mortality rates for nosocomial and community-acquired infections were 2.7 and 2.8 %, respectively. Median length of admission was 14.0 days (Q1: 7 days, Q3: 26 days). Median 90-day cost was $40 861 (Q1: $11 988, Q3: $114, 499) for the nosocomial group and $56 569 (Q1: $26 127, Q3: $142 780) for the community-acquired group. In multivariable regression, the 90-day post-diagnosis total costs were comparable between groups (cost ratio: 0.89; 95 % CI: 0.70 to 1.13), but at 2 years post-diagnosis, the nosocomial group was associated with 137 % higher costs (CR: 2.37, 95 % CI: 1.51 to 3.70). Conclusion. In multivariable analysis, nosocomial infections were associated with significantly higher long-term costs up to 2 years post-infection. Hydrocephalus, intracranial epidural abscess and cerebral oedema were the most common complications, and lumbar punctures and ventricular catheter placement were the most common neurosurgical procedures. This study represents the first nation-wide, longitudinal comparison of the outcomes and considerable HCRU of nosocomial versus community-acquired paediatric BM, including characterization of complications and procedures contributing to the high costs of these infections.